(untitled) - Hanayama, Shinsholl (Tokyo, 1960)
The object of this book is mainly to trace this walk of Buddhism in Japan-to see how it has fared and how it has become Japanese. For, indeed, the Buddhist teaching was always to effect cure with full consideration of the circumstances in which man lives. And this is Mahayanism, which is to see the Buddha's teaching in its spiritual essence
Keywords: Buddhism,Buddhist sects; History; Japan,Japan